Transient Expression of Recombinant Glycoprotein Ibα Polypeptides in COS Cells that Inhibit von Willebrand Factor Binding to the Platelet Glycoprotein Ib/IX Complex - Petersen, Eefke; Handin, Robert I (Thrombosis and Haemostasis, 1992)
The cDNA encoding the glycoprotein Ibα polypeptide has been expressed in COS cells. Transfection with full-length cDNA and a cDNA truncated at an internal Xbal site produced a recombinant polypeptide doublet with estimated molecular weights of 48 and 46 kDa (rGpIbαL318) which could be resolved into a single band of molecular weight 36 kDa following digestion with endoglycosidase F. A portion of the truncated polypeptide was retained in the endoplasmic reticulum of COS cells and slowly released. A second fraction was rapidly secreted into COS cell-conditioned medium and could be used for functional studies. Soluble rGpIbαL318 harvested from COS cell-conditioned medium inhibited ristocetin-dependent binding of [125I]-vWF to fixed washed human platelets (IC50 20 nM). Binding was inhibited by reduction and alkylation of “rGpIbαL318” suggesting the need for a critical disulfide bond to maintain biological activity of the recombinant polypeptide. We conclude that the recombinant polypeptides produced by transfection of GpIbα cDNA into heterologous cells are secreted, soluble, and can inhibit vWF binding to platelet GpIb/IX.